Cancel culture : corporations flock to carbon offsets to solve their climate problem, but do offsets truly reduce emissions? - Isaacs, Andrew M.; Coromina, Natàlia Costa I.; Delgado, Ramon, active 2022 (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2022)
The first market created specifically for carbon offsetting was called the Clean Development Mechanism (CDM) and was established in 1997 as part of the Kyoto Protocol. This agreement, signed by more than 150 countries, aims to reduce greenhouse gas emissions into the atmosphere. Under the CDM, a company can offset its greenhouse gas (GHG) emissions by financing, for example, the construction of a wind or solar power plant instead of a fossil fuel power plant under the CDM. plan. The concept is simple: Although the company providing the fund has not reduced its own emissions, it is paying another company to reduce its emissions, so the company providing the fund will considers some of its own emissions to have been "changed". Since then, companies around the world have significantly increased their carbon offsets, funding many projects seen as beneficial to combating climate change. By 2021, the market will Global carbon has risen sharply, with the value of carbon dioxide (CO2) offsets traded reaching a record $851 billion. The market is expected to continue to grow into 2022 and beyond, as companies around the world announce carbon-neutral goals and other climate commitments that require carbon offsetting purchases.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Carbon offsetting -- Case studies